TINDAK TUTUR PERLOKUSI DALAM ANIME MOVIE YURU CAMP KARYA SUTRADARA YOSHIAKI KYOUGOKU - Welisa Novitri; Meira Anggia Putri (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2023)
Perlocutionary speech acts is a speech act that provides information uttered by a speaker where the utterance contains intentions and objectives that cause an effect or influence based on the utterance. However, there are still many people who find it difficult and confused about the meaning conveyed by the speaker and the meaning understood by the speaker is different from the intention conveyed by the speech partner. This study aims to describe perlocutionary speech acts based on types and sentence forms in the anime movie Yuru Camp by Director Yoshiaki Kyougoku. This type of research is a qualitative research with a qualitative descriptive method. Qualitative research was chosen because the data studied is in the form of utterances that neeed to be explained and described in words. Data collection technique using tapping, listening, and note-taking technique. This research uses the theory of perlocutionary speech acts types and sentence forms according to Yule, and context theory according to Hymes. From the research results, it wa foun that there were 63 data of perlocutionary speech acts which were divided into 5 types and 3 forms of perlocutionary speech acts, namely: 3 data of declaration speech acts, 22 data of directive speech acts, 20 data of expressive speech acts, 11 data of representative speech acts, and 7 data of commissive speech acts. while the forms of sentences are: 42 data of declarative sentence forms, 10 data of imperative sentence forms, and 11 data 0f interrogative sentence forms.